Brand Image Mediating Word of Mouth and Marketing Performance in Aloe Vera MSMEs - Yulita Raporia; Dewi Santika (Target : Jurnal Manajemen Bisnis, 2025)
One of the leading commodities in West Kalimantan is aloe vera. However, the marketing performance of processing aloe vera into food products is still relatively low due to suboptimal marketing strategies. WOM has the potential to improve MSME marketing performance by fostering a positive consumer perception. This study aims to analyze how brand image mediates the relationship between WOM and marketing performance among MSMEs producing processed aloe vera food products in Pon- tianak and Kuburaya. This study uses a quantitative approach, with questionnaires distributed offline. The sample consisted of 115 respondents, and a census method was used. The data were processed using the Structural Equation Modeling (SEM) approach in Analysis of Moment Structures (AMOS) to determine the influence of the relationships among variables. The results of this study show that WOM has a positive and significant effect on brand image and marketing performance. Still, brand image has no effect and is not significant on marketing performance. Brand image is also unable to mediate the effect of WOM variables on the marketing performance of processed aloe vera food MSMEs in Pontianak and Kuburaya. Therefore, MSMES need to improve communication and interaction to make positive WOM a strategy for expanding market share and boosting marketing performance.